Administrative Sanction Caused by non – Compliance with Environmental Standards - Bouslama, Hanene (Journal of Legal Studies and Researches, 2022)
The environmental legal system is particular in adopting an obvious policy to protect the environment and encounter the dangers that constitute environmental violations. The administrative procedures followed by the Algerian legislator are considered the most important sanctions that fall on the polluter in order to bear him the onus of environmental pollution and involving him in funding the costs on which environmental protection.